Affective neuroscience: the foundations of human and animal emotions - Panksepp, Jaak (Series in affective science, 1998)
Some investigators have argued that emotions, especially animal emotions, are illusory concepts outside the realm of scientific inquiry. With advances in neurobiology and neuroscience, however, researchers are proving this position wrong while moving closer to understanding the biology and psychology of emotion. In Affective Neuroscience, Jaak Panksepp argues that emotional systems in humans, as well as other animals, are necessarily combinations of innate and learned tendencies; there are no routine and credible ways to really separate the influences of nature and nurture in the control of behavior. The book shows how to move toward a new understanding by taking a psychobiological approach to the subject, examining how the neurobiology and neurochemistry of the mammalian brain shape the psychological experience of emotion. It includes chapters on sleep and arousal, pleasure and pain systems, the sources of rage and anger, and the neural control of sexuality. The book will appeal to researchers and professors in the field of emotion.